PROPERTIES OF FORMAL STRUCTURES AND SUBSTRUCTURES - Ilman, V. M. (Science and Transport Progress, 2007)
For designing of systems, it has been prposed to use a three-component formal structure with a set of elements, a signature and axiomatics. Some properties of the structures and their substructures have been presented. The problem of recovering the formally grammatical structures with the help of language substructures has been considered.